Non‐ambient X‐ray and neutron diffraction of novel relaxor ferroelectric xBi2(Zn2/3, Nb1/3)O3–(1 – x)BaTiO3. Issue 5 (29th September 2021) - Marshall, Jessica; Walker, David; Thomas, Pamela
Abstract : Combined non‐ambient X‐ray and neutron diffraction have been used to observe lattice parameter convergence in polar phases of the x Bi(Zn2/3 Nb1/3 )O3 –(1 − x )BaTiO3 system below the ferroelectric composition limit at x < 5.0%. The lattice parameter convergence is correlated with peaks in the dielectric and piezoelectric coefficients. Abstract : The first determination of the phase diagram of the novel ferroelectric relaxor x Bi(Zn2/3 Nb1/3 )O3 –(1 −  x )BaTiO3 (BZN‐BT) has been achieved with a combination of high‐resolution X‐ray and neutron diffraction up to the miscibility limit near x (BZN) = 20.0% over a temperature range 20 < T < 400 K. The combined X‐ray and neutron data show that the instability within the x BZN‐(1− x )BT system reaches a maximum at x = 3.9% and is driven by B ‐site displacement and distortion of the oxygen octahedra in the polar phases. Composition‐dependent effects include a narrow Amm 2‐dominated region focused at x = 3.9%, significant convergence of the lattice parameters in both P 4 mm and Amm 2 phases, and sharp maxima in piezoelectric coefficient d 33 and maximum polarization P max . Lattice parameter dilation at x ≥ 4.0% was observed for both P 4 mm and Amm 2 unit cells, alongside the first appearance of Pm 3 m at 295 K and the onset of significant dielectric relaxation. Low‐temperature neutron diffraction indicated a weak or non‐existent temperature dependence on the transition from ferroelectric at x = 3.9% to ferroelectric relaxor at x = 4.0%. Temperature‐dependent phase transitions were eliminated near x = 3.0%, with the ferroelectric limit observed at x = 5.0% and a transition to a low‐loss relaxor dielectric near x = 8.0%.